Data on differentially expressed miRNAs in dogs infected with Leishmania infantum - Bragato, Jaqueline Poleto [UNESP]; Melo, Larissa Martins [UNESP]; Venturin, Gabriela Lovizutto [UNESP]; Rebech, Gabriela Torres [UNESP]; Garcia, Leandro Encarnação [UNESP]; Lopes, Flavia Lombardi [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Elsevier, 2018)
This paper contains data on differentially expressed miRNAs in peripheral blood mononuclear cells (PBMC) of dogs naturally infected by Leishmania (L.) infantum compared to healthy dogs. In recent years, studies with miRNAs have shown that these molecules play a critical role in the regulation and function of immune response.Differentially expressed miRNAs were identified by microarray, validated by real time PCR and compared with parasite load in the dogs. Targets and pathways were analyzed using the Ingenuity Pathway Analysis program.
Keywords: Dog; Leishmania infantum; miRNA